Telling a 'good or white lie': The views of people living with dementia and their carers. (November 2020) - Casey, Dympna; Lynch, Una; Murphy, Kathleen; Cooney, Adeline; Gannon, Mary; Houghton, Catherine; Hunter, Andrew; Jordan, Fionnuala; Smyth, Siobhan; Felzman, Heike; Meskell, Pauline
Objective: A common symptom of cognitive decline in people living with dementia, or people with memory problems, the cause of which has not yet been diagnosed, is the person repeatedly asking for loved ones who are deceased or making statements that are incorrect. Carers are then faced with a dilemma, do they avoid and distract or 'correct' the person and tell the 'truth', or tell a lie. This paper explores the concept of lying from the perspective of people living with dementia in the community and their informal/unpaid carers. Methods: A descriptive qualitative study utilising focus groups to collect the data was conducted. Three focus group's with a purposive sample of people with memory problems ( n = 14) and three focus group's with informal/unpaid carers ( n = 18) were undertaken. Qualitative content analysis was used to analyse the data. Results: All participants considered that blatant lying with the intention to deceive and do harm is not acceptable. However, telling a 'good lie' or 'white lie' to alleviate distress was in certain circumstances considered acceptable. The intention behind the 'lie' in their view had to be to do good, and the informal/unpaid carer telling the lie had to really 'know the person' and be cognisant of family preferences. Some informal/unpaid carers acknowledged that it may be acceptable for health care professionals to tell a 'good lie' or 'small lie' in certain circumstances. However, health professionals need to 'know the person' and need to consider informal/family caregivers' wishes. Conclusion: Lying was only considered acceptable in the context of knowing the person and when done with the intention not to harm or deceive, undertaken with empathy, and only for the purpose of mitigating the person living with dementia's distress.